Agronomic traits and control of root diseases of wheat, in rotation with other winter crops - Pereira dos Santos, Henrique; Cesar Barreneche Lhamby, Julio; Moraes Prestes, Ariano; Melo Reis, Erlei (Pesquisa Agropecuaria Brasileira, 1998)
During nine years, in Passo Fundo, RS, Brazil, the effect of crop rotation systems on yield, root diseases, and some agronomic traits of wheat (Triticum aestivum L.) were assessed. Six rotation systems for wheat were studied: monoculture; one winter without wheat, from 1990 to 1995; two winters without wheat; three winters without wheat; two winters without wheat and two winters with wheat; and three winters without and two winters with wheat. The winter crops were sown to conventionally prepared soil, and summer crops were set up under no-till. An experimental design of blocks at random was used, with three replications and plots totalling 30 m2. Crop rotation was efficient in reducing root diseases and in increasing wheat yields. No significant differences were observed among the systems used, indicating that wheat can be sown with one winter of crop rotation (wheat/soybean and common vetch/corn) only. Additionally, wheat can be sown in two consecutive winters, if two winters are left in rotation (wheat/soybean, wheat/soybean, white oats/soybean, and common vetch/corn). When comparing with the rotation systems, it became evident that the number of spikes, number of grains, and grain weight were significantly reduced by monoculture.